Habilidades técnico-interpretativas ao fagote para a performance da Ciranda das sete notas (Fantasia para fagote e quinteto de cordas) de Villa-Lobos - Arruda, Felipe dos Santos (2016)
Heitor Villa-Lobos brings significant new prospects for the bassoonist. Within this context this paper presents an investigation of the technical and interpretative skills necessary to perform the Ciranda das sete notas (Fantasy for bassoon and string quintet) by Villa-Lobos. The musical elements articulation, sound production, embouchure, breathing and fingering are based on the concepts presented by Julius Weissenborn (1887), Ludwig Milde (1950) Fernand Oubradous (1988), Gallois (2009) and the physiologist Fox (2007). The discussions are grounded on the above concepts and personal experience of the author in preparation to perform the Ciranda. Some excerpts were selected which expose mastery of technical skills for interpretation. It was found that there is a wealth of skills demanded in this Brazilian work, which enables the development of music skills equal to traditional foreign repertoire for the bassoon. This research shows the lack of literature, especially in Portuguese, with deep approach to the technical and interpretative elements - articulation, sound, embouchure, breath and fingering - for the bassoon player. In addition, a bassoonist who wants to interpret this work should: have knowledge of the sound characteristics of different regions of the bassoon for decision-making purposes of interpretation; master the skills related to playing legato in large intervals; be able to play staccato and legato throughout the whole extension of the bassoon. During the recital preparation I also noted that the above skills are recurring features present on Villa-Lobos other compositions, which makes the discussions presented here useful for application in the interpretation of other works of the composer.